2018
DOI: 10.1016/j.bcp.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endocannabinoid system in drug addiction

Abstract: Drug addiction is a chronic relapsing disorder that produces a dramaticglobal health burden worldwide. Not effective treatment of drug addiction is currently available probably due to the difficulties to find an appropriate target to manage this complex disease raising the needs for further identification of novel therapeutic approaches. The endocannabinoid system has been found to play a crucial role in the neurobiological substrate underlying drug addiction. Endocannabinoids and cannabinoid receptors are wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 232 publications
(385 reference statements)
2
83
0
3
Order By: Relevance
“…Furthermore, OPRM1 modulates dopamine transmission within the cortico‐mesolimbic system . Besides, CB 1 r plays an essential role in alcohol addiction, being involved in different processes such as decision‐making, alcohol withdrawal, and relapse . Thus, the results obtained here agree with previous reports showing an upregulation of TH gene expression in the VTA under acute or chronic alcohol administration and highlight the role of OPRM1 mediating the rewarding properties of ethanol .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, OPRM1 modulates dopamine transmission within the cortico‐mesolimbic system . Besides, CB 1 r plays an essential role in alcohol addiction, being involved in different processes such as decision‐making, alcohol withdrawal, and relapse . Thus, the results obtained here agree with previous reports showing an upregulation of TH gene expression in the VTA under acute or chronic alcohol administration and highlight the role of OPRM1 mediating the rewarding properties of ethanol .…”
Section: Discussionsupporting
confidence: 91%
“…The second important finding in this study is the involvement of CB 2 receptors in nicotine self‐administration in mice. An exciting body of literature provides compelling evidence that the eCB system interacts with brain reward circuits and is implicated in drug reward and addiction (Jordan & Xi, ; Manzanares et al, ). As CB 1 receptors are highly expressed in the brain, early studies focused on the involvement of these receptors in drug reward, including nicotine reward and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that, in addition to CB 1 receptors, the CB 2 receptors are also involved in drug reward, including nicotine reward and dependence (Jordan & Xi, ; Manzanares et al, ). In the present study, we found that CB2‐KO mice displayed significantly lower nicotine self‐administration than their WT littermates (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CB2r, the main cannabinoid receptors in peripheral immune cells (Fernández-Ruiz et al, 2007; Schmöle et al, 2015a), are found in monocytes, macrophages and lymphocytes, and their expression increases in conditions of active inflammation (Schmöle et al, 2015b; Shang and Tang, 2017). The presence of CB2r in the nervous system was thought to be restricted to microglia and limited to pathological conditions or intense neuronal activity (Manzanares et al, 2018). However, recent studies using electrophysiological approaches and tissue-specific genetic deletion revealed functional CB2r also in neurons, where they modulate dopamine-related behaviors (Zhang et al, 2014) and basic neurotransmission (Quraishi and Paladini, 2016; Stempel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%